2016
DOI: 10.1021/acs.jpca.6b04282
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Transformations in Aromatic Nitroso Oxides

Abstract: A systematic theoretical study on conformational transformations of monosubstituted (ortho- and para-) aromatic nitroso oxides R-C6H4NOO was performed. The existence of two rotation axes enables two types of conformational transitions in substituted arylnitroso oxides: trans/cis (rotation around the N-O bond) and syn/anti (rotation around the C-N bond, which is important in ortho isomers). The complete set of conformers was localized for R-C6H4NOO using four selected density functional (M06-L, mPWPW91, OLYP, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…In other cases, the planarity of the NOO fragment is preserved. It was found that the cis and trans states of 2a have close energies, which is consistent with the results reported in the work of ref for a number of para- and ortho-substituted phenylnitroso oxides.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In other cases, the planarity of the NOO fragment is preserved. It was found that the cis and trans states of 2a have close energies, which is consistent with the results reported in the work of ref for a number of para- and ortho-substituted phenylnitroso oxides.…”
Section: Discussionsupporting
confidence: 91%
“…This result is not associated with an error of the theoretical estimation of the activation barriers using the M06-L functional. Indeed, the difference in the activation energies of the ortho-cyclization ΔΔ G ⧧ = Δ G ⧧ (cis / anti) – Δ G ⧧ (cis / syn) were recalculated using mPWPW91 and HCTH density functionals, the applicability of which when describing properties of nitroso oxides was demonstrated in the work of ref . In all cases, the ΔΔ G ⧧ values were in the interval from 16 to 19 kJ/mol.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our experimental data clearly provide evidence for the existence of a peroxy intermediate (vide supra), although its structure is uncertain at present. Based on our experimental data, the peroxy intermediate in the nitrosamine– 3 O 2 photoreaction is less reactive compared to carbonyl oxide and nitroso- O -oxide that appear in ozonolysis and triplet nitrene– 3 O 2 reactions, respectively, due to the latter’s ability to oxidize solvents such as toluene …”
Section: Resultsmentioning
confidence: 88%
“…An acceptable alternative to multiconfigurational calculations is use of the density functional theory (DFT) methods. In the work of ref , a careful selection of a DFT method for investigation of the structure, spectral, and energetic properties of aromatic nitroso oxides was performed. It was shown that the M06-L functional in conjunction with the Pople basis set of triple valence splitting 6-311+G­(d, p) adequately describes the abovementioned properties.…”
Section: Methodsmentioning
confidence: 99%
“…The full optimization of the structures of isomeric forms and transition states of irreversible transformations of aromatic nitroso oxides under study has been carried out . The correspondence of the found structures to the minima on the potential energy surface was established by the absence of negative elements in the diagonalized Hessian matrix, while the presence of the only negative element testified that the structure corresponds to the transition state.…”
Section: Methodsmentioning
confidence: 99%